Validation of the oral health version of the Instrument for Diagnosis of the Developmental Stage of the Healthcare Network - Leal, Daniele Lopes (2019)
OBJECTIVE: To validate the oral health version of the Instrument for Diagnosis of the Developmental Stage of the Healthcare Network. MATERIALS AND METHODS: The sample was comprised of the oral health coordinators from 154 municipalities in Minas Gerais State, Brazil, chosen for convenience. The oral health version of the Instrument was previously submitted to the adaptation stage, and then the field test phases and the study of the psychometric properties of the Instrument (reliability and validity) were conducted. Questionnaires were sent to the coordinators by email. RESULTS: Internal consistency for the total score (Cronbach's alpha coefficient = 0.97) and domains (Cronbach's alpha coefficient = 0.77-0.94) was demonstrated. Test-retest reported good stability based on the analysis of the total score (intraclass correlation coefficient - ICC = 0.88) and domains (ICC = 0.83-0.91). Percentage agreement of the items showed construct validation, varying from regular to almost perfect (r s between 0.25 and 0.81). For discriminant validity, total score and three domains, Population, Logistical systems and Network Governance System distinguished the groups according to the time of formation (p ≤ 0.05). CONCLUSION: The oral health version of the Instrument showed adequate psychometric properties regarding the reliability and validity of the construct and discriminant.